Oxidative Stress and DNA Methylation in Prostate Cancer - Krishna Vanaja Donkena; Charles Y. F. Young; Donald J. Tindall (Obstetrics and Gynecology International)
The protective effects of fruits, vegetables, and other foods on prostate cancer may be due to their antioxidant properties. An imbalance in the oxidative stress/antioxidant status is observed in prostate cancer patients. Genome oxidative damage in prostate cancer patients is associated with higher lipid peroxidation and lower antioxidant levels. Oxygen radicals are associated with different steps of carcinogenesis, including structural DNA damage, epigenetic changes, and protein and lipid alterations. Epigenetics affects genetic regulation, cellular differentiation, embryology, aging, cancer, and other diseases. DNA methylation is perhaps the most extensively studied epigenetic modification, which plays an important role in the regulation of gene expression and chromatin architecture, in association with histone modification and other chromatin-associated proteins. This review will provide a broad overview of the interplay of oxidative stress and DNA methylation, DNA methylation changes in regulation of gene expression, lifestyle changes for prostate cancer prevention, DNA methylation as biomarkers for prostate cancer, methods for detection of methylation, and clinical application of DNA methylation inhibitors for epigenetic therapy.